SCIENTIFIC ATTITUDE IDENTIFICATION AND INTEREST OF PURSUING CAREER IN THE PHYSICS - Sukarni, Weni; Jannah, Nurdatul; Qoriyana, Dina; Zain, Muhammad Sofyan (Tarbiyah : Jurnal Ilmiah Kependidikan, 2020)
The purpose of the research to identification attitudes of students SMAN 08 Batanghari of Physics on two indicators, that is the adoption of scientific attitudes and career interests in Physics. The sample used was 150 students. This type of research is quantitative with survey methods. The instrument used was an attitude questionnaire. Data analysis in this study uses descriptive statistics. The results obtained showed that the Adoption Indicator of scientific attitudes had the highest percentage of 69.3% with a good category and indicators of career interests in Physics had the highest percentage of 55.3% with a quite good category.